Peran Vascular Endothelial Growth Factor (VEGF) dalam Patogenesis Spektrum Plasenta Akreta 1 - Linggodigdo, Michelle; Hellyanti, Tantri; Kusmardi (Majalah Patologi Indonesia, 2022)
Placenta accreta spectrum (PAS) is a cause of serious maternal morbidity and mortality. FIGO 2020 designated PAS into grade 1 (non-invasive), grade 2 (superficial invasion), grade 3A (deep invasion), grade 3D (deep invasion with disruption of the serosa), and grade 3E (deep invasion with adherence to extrauterine structures). Currently, the trophoblast cell in accreta spectrum is associated with similar characteristics to cancer. Both conditions can induce angiogenesis, marked by upregulation of vascular endothelial growth factor (VEGF). This resulted in the formation of extensive neovascularization. The secretion of VEGF is induced by hypoxia, which was related to risk factor of PAS occurrence; defect of the decidua due to endometrial tissue damage.